HTML5 Based Ajax and SSE Technology with Server Intelligent Instant Messaging to Meet the Needs of Transactional Websites - Li Shuangyuan (ITM Web of Conferences, 2019)
With the continuous development of science and technology, Internet technology has been quietly affect the mode of transmission, traditional web site information data only through the web page to load when it is open, need to update the web page information can only be accomplished by way of a page refresh. In today's efficient informatization environment, has highlighted its problems, restricted information updated timely. In this paper, the new Internet programming language of HTML5 is combined with Ajax and SSE technology to study intelligent instant messaging and realize the new application mode.